Integrated and Sustainable Transit Development: A Case Study of Terminal Isimu and Djalaluddin Airport in Gorontalo Province - Rahmawati, Aisyah; Nasrullah, Muhammad Nur Cahyo Hidayat; Mintje, Quirina Ariantji Patrisia (Logistica : Journal of Logistic and Transportation, 2025)
This study examines the integration potential between Terminal Isimu and Djalaluddin Airport in Gorontalo Province, Indonesia, using the Green Transport Sustainability Model (GTSM). The research evaluates existing conditions of intermodal connectivity, identifies key barriers, and develops alternative development scenarios. A qualitative descriptive approach was applied, relying on secondary institutional data and GTSM indicators such as connectivity, modal share, emissions, and stakeholder alignment. The findings indicate that Terminal Isimu currently operates as an informal hub, while Djalaluddin Airport serves growing passenger and cargo traffic with limited coordination. Three scenarios are outlined, ranging from basic shuttle linkage to a full Transit Oriented Development (TOD) with electric vehicles and intelligent transport systems. The study contributes by contextualizing GTSM in a secondary city setting and highlighting practical pathways for phased integration. However, the exclusive use of secondary data and the absence of field validation limit the scope of findings. Future research should incorporate surveys or stakeholder engagement to strengthen empirical evidence and ensure policy relevance. The study concludes that Gorontalo holds significant promise as a model for sustainable transit integration in Indonesia's secondary urban areas. Through strategic investments and stakeholder collaboration, the region can enhance accessibility, reduce emissions, and support inclusive economic growth.